The Effectiveness of Maggot (Hermetia Illucens) Growth in Various Growing Media - Nur'aini, Nur'aini; Prawanto, Andika (Talenta Publisher, 2021)
Utilization of maggot as a substitute for protein source feed ingredients can be a solution to overcome the high cost of feed. However, the inappropriate growth media caused the growth of maggots to be inhibited. Palm kernel cake, vegetable and fruit waste have high nutritional content which has the potential as a medium for growing maggots. The purpose of this study was to determine the best growth of maggot on various growing media. The treatments given in this study were P0A = 100% palm kernel cake; P0B = 100% vegetable and fruit waste; P1 = palm kernel cake 75% + vegetable and fruit waste 25%; P2 = palm kernel cake 50% + vegetable and fruit waste 50%; P3 = palm kernel cake 25% + vegetable and fruit waste 75%. The results showed that the use of growing media from mixing 25% palm kernel cake + 75% vegetable and fruit waste (P3) gave better results as a growth medium for the effectiveness of the growth of maggot. This is due to the nutritional needs of maggots for its growth have been met from the nutritional content and organic matter available in optimum quantities in the growing media. It was concluded that the growing media from palm kernel cake with vegetable and fruit waste had effectiveness in increasing the growth of maggot.